2016
DOI: 10.1088/0967-3334/37/9/n62
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in the military: towards a fatigue detection test based on the saccadic velocity

Abstract: Fatigue is a major contributing factor to operational errors. Therefore, the validation of objective and sensitive indices to detect fatigue is critical to prevent accidents and catastrophes. Whereas tests based on saccadic velocity (SV) have become popular, their sensitivity in the military is not yet clear, since most research has been conducted in laboratory settings using not fully validated instruments. Field studies remain scarce, especially in extreme conditions such as real flights. Here, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Di obtained similar results by finding the metric saccadic velocity decreased after long simulated flights in comparison to short simulated flights. The authors suggested saccadic velocity as a biomarker for aviator fatigue as did Diaz-Piedra et al (2016) for warfighter fatigue. McKinley et al (2011) evaluated two kinds of eye metrics-namely total eye closure duration and approximate entropy-to detect fatigue in tasks relevant to military aviation after sleep deprivation (14-28 hr).…”
Section: Health and Physiological Factors Affecting Performancementioning
confidence: 99%
“…Di obtained similar results by finding the metric saccadic velocity decreased after long simulated flights in comparison to short simulated flights. The authors suggested saccadic velocity as a biomarker for aviator fatigue as did Diaz-Piedra et al (2016) for warfighter fatigue. McKinley et al (2011) evaluated two kinds of eye metrics-namely total eye closure duration and approximate entropy-to detect fatigue in tasks relevant to military aviation after sleep deprivation (14-28 hr).…”
Section: Health and Physiological Factors Affecting Performancementioning
confidence: 99%
“…Notably, studies that have had success at linking fatigue and saccadic velocity, have operationalised fatigue as a reduced alertness/vigilance. Most of these studies, commonly report a relationship between reduced alertness with a decrease in saccadic velocity [10]. If self-report symptoms of visual fatigue after VR-exposure are linked to alertness instead of symptoms of visual dysfunction, then it is possible that visual fatigue after VR has cognitive origins [7].…”
Section: Introductionmentioning
confidence: 99%
“…This temporary dissociation of vergence and accommodation introduces unnatural conflicts in visual processing, which are linked to symptoms such as headaches and visual fatigue. a relationship between reduced alertness with a decrease in saccadic velocity (10). If self-report symptoms of visual fatigue after VR-exposure are linked to alertness instead of symptoms of visual dysfunction then it is possible that visual fatigue after VR has cognitive origins (7).…”
Section: Introductionmentioning
confidence: 99%